Yield potential and persistency of cocksfoot and tall fescue in mixtures with lucerne at different levels of nitrogen fertilization - Nesic Z.; Tomic Z.; Krnjaja V.; Ruzic-Muslic D. (Sustainable Mediterranean grasslands and their multi-functions, 2008)
In order to determine the suitability of cocksfoot and tall fescue with lucerne in mixture at a certain level of N fertilization, a mixture of lucerne, cocksfoot and tall fescue was seeded and four different N fertilization levels (0, 70, 140, 210) were applied. The results were monitored in the second year of investigation. Cocksfoot has proven to be more persistent and with higher yields of grass for cultivation in mixture with lucerne compared to tall fescue. Control treatments had a better effect on lucerne, whereas in treatments with N, especially N 210, grasses improve their competitive abilities and increase productivity. Considering individual cuts, cocksfoot was present more frequently than tall fescue during the whole vegetation season and uniformity of yields per cuts for certain fertilization treatments diminished in the N210?N0 direction. Competitive ability is a very important characteristic of species that make up grass-leguminous mixtures.
12. Meeting of the Sub-Network on Mediterranean Forage Resources of the FAO-CIHEAM Inter-regional Cooperative Research and Development Network on Pastures and Fodder Crop, 2008/04/09-12, Elvas (Portugal)